A Unified Account of General Learning Mechanisms and Theory‐of‐Mind Development. (March 2014) - BACH, THEODORE
Abstract Modularity theorists have challenged that there are, or could be, general learning mechanisms that explain theory‐of‐mind development. In response, supporters of the 'scientific theory‐theory' account of theory‐of‐mind development have appealed to children's use of auxiliary hypotheses and probabilistic causal modeling. This article argues that these general learning mechanisms are not sufficient to meet the modularist's challenge. The article then explores an alternative domain‐general learning mechanism by proposing that children grasp the concept belief through the progressive alignment of relational structure that occurs as a result of structural‐comparison. The article also explores the implications of the proposed account for Fodor's puzzle of conceptual learning.